2001
DOI: 10.1152/ajprenal.2001.280.5.f844
|View full text |Cite
|
Sign up to set email alerts
|

SFKs, Ras, and the classic MAPK pathway couple muscarinic receptor activation to increased Na-HCO3cotransport activity in renal epithelial cells

Abstract: Cholinergic agents are known to affect the epithelial transport of H2O and electrolytes in the kidney. In proximal tubule cells, cholinergic agonists increase basolateral Na-HCO(3) cotransport activity via M(1) muscarinic receptor activation. The signaling intermediates that couple these G protein-coupled receptors to cotransporter activation, however, are not well defined. We therefore sought to identify distal effectors of muscarinic receptor activation that contribute to increased NBC activity in cultured p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 37 publications
3
29
0
Order By: Relevance
“…It has been suggested that desensitization, associated with downregulation of β-adrenoceptors induced by a β-adrenoceptor agonist, is related to the translocation of the β2-adrenoceptor out of caveolae and that this translocation might cause a sequestration of the receptor from the effector, contributing to a reduction in the efficiency of β2-adrenoceptor coupling to AC (Ostrom et al, 2001). Caveolae play a pivotal role in compartmentalizing GRKs, potentially providing a mechanism for rapid activation/inactivation of GRKs that may be necessary in certain signalling situations, such as receptor desentitization (Robey et al, 2001). In addition, indacaterol shows a greater affinity for caveolae and could maintain the efficiency of β-adrenoceptor-linked effectors, reducing desensitization by interacting with caveolae (Lombardi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that desensitization, associated with downregulation of β-adrenoceptors induced by a β-adrenoceptor agonist, is related to the translocation of the β2-adrenoceptor out of caveolae and that this translocation might cause a sequestration of the receptor from the effector, contributing to a reduction in the efficiency of β2-adrenoceptor coupling to AC (Ostrom et al, 2001). Caveolae play a pivotal role in compartmentalizing GRKs, potentially providing a mechanism for rapid activation/inactivation of GRKs that may be necessary in certain signalling situations, such as receptor desentitization (Robey et al, 2001). In addition, indacaterol shows a greater affinity for caveolae and could maintain the efficiency of β-adrenoceptor-linked effectors, reducing desensitization by interacting with caveolae (Lombardi et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Wortmannin was able to inhibit tubular basolateral transport of PAH in isolated proximal tubules from rabbit kidney (4) and to inhibit apical P-glycoprotein-mediated drug efflux in the proximal tubule of mice (38). The involvement of G receptor-linked stimulation of MAPK activity was also demonstrated for the regulation of Na-HCO 3 Ϫ cotransport activity after muscarinic stimulation by carbachol in the opossum kidney proximal tubule cell line (28). The components of the signaling pathway of G proteincoupled receptors downstream of PI3K probably have no influence on hOCT2 activity, because inhibition of MEK1 and MEK2 by UO126 had no effect on basal ASP ϩ transport or on carbachol-induced inhibition of ASP ϩ uptake.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that ERK1/2 can regulate other ion transporters independently of NHE-1. The possible targets for ERK1/2 that could contribute to the cytosolic Na ϩ and Ca 2ϩ load include the Na ϩ -K ϩ -2Cl Ϫ cotransporter, which is activated by ␣ 1 -adrenergic agonist in an ERK1/2-dependent mechanism in cardiac myocytes (2), or the Na ϩ -HCO 3 Ϫ cotransporter, which is coupled to muscarinic receptor activation by ERK1/2 in renal epithelial cells (30). We cannot rule out the possibility that ERK1/2 can directly modulate NCX or Na ϩ /K ϩ pump activity that could also contribute to alterations in Ca 2ϩ or Na ϩ homeostasis.…”
Section: Discussionmentioning
confidence: 99%